A road map for explorative scenario creation on Belgian rail freight transport development. Issue 1 (March 2017) - Troch, Frank; Vanelslander, Thierry; Sys, Christa; Laroche, Florent; Merchan, Angel; Mostert, Martine; Stevens, Vidar; Tawfik, Christine; Belboom, Sandra; Léonard, Angélique; Limbourg, Sabine; Verhoest, Koen
The starting point of this article is the weak usage of rail freight in Belgium and Europe, both as a sustainable mode of land transportation in itself as well as a part of the intermodal chain. The results are obtained by transversal research on rail freight transport in Belgium, taking into account the European context. This interdisciplinary research develops a road map for the creation of three integrated scenarios: a best case, medium case and worst case scenario for rail freight development, based on a detailed SWOT (strength, weakness, opportunities, threats) analysis. It includes the most probable future developments for rail freight transport and hinterland connections. These developments are obtained from literature review and discussions with a heterogeneous panel of experts in the fields of (i) optimal corridor and hub development, (ii) macroeconomic impact, (iii) sustainability, (iv) effective market regulation and (v) governance and organization for a well-functioning intermodality. The Delphi approach is used in combination with a survey analysis. Frequency tables and the H-index allow defining a ranking and selection of SWOT elements. The obtained scenarios allow future research to quantify and measure the impact of future developments and decisions towards the Belgian rail freight market.